Analisis Pembelajaran Projek Penguatan Profil Pelajar Pancasila di SDN 27 Batu Buil - Nurhidayah, Widia; Mastiah; Moh Kusuma Atmaja, Nur (putrapublisher.org, 2025)
This study aims to analyze the implementation of learning project strengthening Pancasila student profile (P5) with the theme of Sustainable Lifestyle at SDN 27 Batu Buil. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers have designed and implemented P5 learning contextually by actively involving students through waste sorting project activities. Students show high enthusiasm, work together in groups, and produce creative works from recycled materials. Evaluation is carried out verbally and using a simple rubric, while reflection is carried out through discussion and presentation. There are changes in student behavior in maintaining cleanliness and sorting waste according to its type. This learning has a positive impact on the clean culture in schools and encourages students to apply the values of the Pancasila student profile in everyday life. This study recommends the continuation of the program and broader involvement between schools, teachers, students, and parents.